2014
DOI: 10.1247/csf.14001
|View full text |Cite
|
Sign up to set email alerts
|

Plk1 Phosphorylates CLIP-170 and Regulates Its Binding to Microtubules for Chromosome Alignment

Abstract: ABSTRACT. The microtubule (MT) cytoskeleton is essential for cellular morphogenesis, cell migration, and cell division. MT organization is primarily mediated by a variety of MT-associated proteins. Among these proteins, plus-end-tracking proteins (+TIPs) are evolutionarily conserved factors that selectively accumulate at growing MT plus ends. Cytoplasmic linker protein (CLIP)-170 is a +TIP that associates with diverse proteins to determine the behavior of MT ends and their linkage to intracellular structures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Recombinant GST-fused proteins were produced in Escherichia coli (XL-1 blue, BL21DE3, or RosettaDE3) using isopropyl-β- d -thiogalactopyranoside and were purified as described previously ( Wang et al, 2012 ; Kakeno et al, 2014 ). To produce GST, GST-EB1, and GST-EB3, we used pGEX (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant GST-fused proteins were produced in Escherichia coli (XL-1 blue, BL21DE3, or RosettaDE3) using isopropyl-β- d -thiogalactopyranoside and were purified as described previously ( Wang et al, 2012 ; Kakeno et al, 2014 ). To produce GST, GST-EB1, and GST-EB3, we used pGEX (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…The end-tracking assay was performed as previously described ( Kakeno et al, 2014 ). Flow chambers (22 mm wide × 1 mm high × 0.15 mm deep) were assembled between a coverslip and a precleaned glass microslide using double-sided tape.…”
Section: Methodsmentioning
confidence: 99%
“…However, CLIP-170 inhibition does not seem to affect kinetochore microtubule dynamics or stability, possibly because it is stripped from the kinetochore by Dynein upon the establishment of end-on kinetochore-microtubule attachments [103,104]. Moreover, phosphorylation of CLIP-170 at S312 by Plk1 regulates its binding to microtubules and is crucial for chromosome alignment [105]. CLIP-170 appears to promote kinetochore-microtubule attachments and chromosome congression by counteracting Dynein/Dynactin [106].…”
Section: Mechanisms Of Chromosome Congressionmentioning
confidence: 99%
“…CLIP-170 is thought to facilitate KT-MT attachment by binding to microtubules through its N-terminus, which contains cytoskeleton-associated protein-glycine-rich (CAP-Gly) domains (Tanenbaum et al, 2006). Recently, it was reported that PLK1 also phosphorylates CLIP-170 at S312, which regulates the binding of CLIP-170 to microtubules and is pivotal for chromosome alignment (Kakeno et al, 2014). Therefore, PLK1 recruitment by CLIP-170 is expected to promote KT-MT attachment directly through CLIP-170 by regulating the kinetochore localization and microtubule-binding activity of the latter.…”
Section: Plk1 Recruitment To Kinetochores Is Dependent On Cdk1 Phosphmentioning
confidence: 99%